I want to break free: a phenomenological study of entrepreneurs’ experiences of freedom - Manzoli, Ana Carolina Jacob (2023)
What drives and inspires young people to get into entrepreneurship is widely researched. However, most studies addressing the motivation for entrepreneurship are based on organizational psychology and take an objectivist and cognitive approach. In contrast with this literature, my study is from an intersubjectivist ontological and a subjectivist epistemological position and is informed methodologically by phenomenological perspective that focuses on lived experience. My study aims to answer the following research question: "What does the experience of freedom mean for young entrepreneurs?” I gathered empirical material through participant-led photo-elicitation methods and in-depth semi-structured interviews. I contribute to the field of entrepreneurial studies theoretically and methodologically in the following way: a) Theoretically: extending literature on entrepreneurial motivation and entrepreneurial intention by offering a deeper and broader understanding of freedom. The former is primarily concerned with a specific element of freedom: autonomy, whereas the study findings offer a fruitful and profound understanding of how entrepreneurs experience freedom as relational, transitory, and contradictory; b) Methodologically: by bringing a rarely used perspective to the field of entrepreneurship, that of phenomenology, which is based on an intersubjectivist ontology and a subjectivist epistemology. Consequently, understanding how entrepreneurs experience freedom could help people make better and more informed career choices.